Estudio de factibilidad para la creación de una empresa de producción de asadores ecológicos y su comercialización en el cantón Palora, provincia de Morona Santiago - Martínez, Gloria de Los Ángeles (2014)
The objective of this research is the creation Organize a production of organic roasters for marketing in the canton Palora province of Morona Santiago which allowed the application of different methods and techniques allows for the investigation, as the method deductive which is the more usual scientific method, which is characterized by four basic steps: observation and recording of all the facts: the analysis and classification of facts; inductive derivation of a generalization from the facts; and the contrast, the inductive method which the particular part to reach is usually so by studying the various parts that comprise an assessment of the project failed to win the general conclusion as the feasibility of the project, Statistical method which consists of a set of procedures for managing qualitative and quantitative research data. This data management purpose is to check, in a part of the reality of one or more vertical consequences deduced from the general and specific objectives of the research. The use of these methods allowed to reach the culmination of this work and that to do had to follow the steps of understanding and application of the same show. The use of these methods allowed to reach the culmination of this work and that to do had to follow the steps of understanding and application of the same show. In the market survey in the canton Palora, with a sample of 326 people and 5 trading; Weighted surveys have been analyzed and the results have been inferred and then perform market analysis, determining the potential demand of 1,068 households, 1,025 families Demand Real, Effective Demand 810 families who buy 186 broiler, The Offer of 114 broiler unmet demand and 72 broilers, which allowed us to determine that the project can and should be performed by the results obtained in the analysis of demand, supply and levels of marketing this product. The installed capacity of the project determines that the company will be able to produce 70 broilers and whose capacity utilization is 60 broilers, of which 50 % of the capacity used for the first year, corresponding to 60 broilers occur also determined the location thereof to be located in the city of Palora, streets Coca River and Venezuela. The production process requires the use of suitable equipment, which will be guaranteed to get a quality product at reasonable prices. Then determining the project engineering process diagrams, characteristics of operation and management, technical requirements as equipment, facilities, furniture and fixtures develops. Also an administrative study determined as a Limited Liability Company, and functional organizational structure to the hierarchical levels both Legislative, Executive, Consultant Level Support Assistant, Level Operational Level and the operating manuals, charts was performed; which served as a guideline for implementing a good organization, because it will have the following staff : Manager, a Secretariat a Concierge - Guardian, one Accountant who will be part of the Administrative staff and operational staff distributed as follows: a Head production, a Head of Sales, Two Workers, and a seller. The project reaches an investment of $ 20,749.25 and will be funded with contributions from partners the 51.81 % of total investment corresponding to $ 10,749.25 and a loan to keep the project with the Development Bank will be the corresponding to 48.19 % $ 10,000 10-year term at 15 % annual interest. The financial evaluation shows the following results: According to the NPV of this project gives a positive value of $ 31,898.39, indicating that the project or investment is suitable. For this project, the IRR is 44 % and this satisfactory value to implement the project, the time required to recover the initial investment would be two years, five months and 15 days to this project, the sensitivity values are lower you therefore do not affect changes in project costs and revenues increased 34.50% and decreased by 23.80%, respectively, ie the project is not sensitive to these changes. Then the most significant findings and recommendations of the project arises